2017
DOI: 10.1111/bph.13720
|View full text |Cite
|
Sign up to set email alerts
|

Morroniside, a secoiridoid glycoside from Cornus officinalis, attenuates neuropathic pain by activation of spinal glucagon‐like peptide‐1 receptors

Abstract: Our data demonstrated that morroniside was an orthosteric agonist of GLP-1 receptors and produced antihypersensitivity in a neuropathic pain model by activation of spinal GLP-1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…IL-10 has been considered the most important anti-inflammatory cytokine so far studied, and acts by binding to the IL-10 receptor-␣ followed by activation of IL-10 receptor-␤ localized on the cell membrane (Sabat et al, 2010;Glocker et al, 2011). Exogenous application of IL-10 exhibited antinociceptive activities in sciatic nerve chronic constriction injury-and paclitaxel-induced neuropathic pain, formalin-and CFA-induced inflammatory pain, bone cancer pain, and diabetic neuropathic pain (Milligan et al, 2005;Ledeboer et al, 2007;Zhou et al, 2008;Kim et al, 2011;Thakur et al, 2016). In the current study, multiple daily intrathecal injections of siRNA/IL-10 receptor-␣ progressively induced mechanical allodynia in the contralateral hindpaws, although it did not further attenuate the reduced withdrawal thresholds in the ipsilateral paws, which may be due to the ceiling effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IL-10 has been considered the most important anti-inflammatory cytokine so far studied, and acts by binding to the IL-10 receptor-␣ followed by activation of IL-10 receptor-␤ localized on the cell membrane (Sabat et al, 2010;Glocker et al, 2011). Exogenous application of IL-10 exhibited antinociceptive activities in sciatic nerve chronic constriction injury-and paclitaxel-induced neuropathic pain, formalin-and CFA-induced inflammatory pain, bone cancer pain, and diabetic neuropathic pain (Milligan et al, 2005;Ledeboer et al, 2007;Zhou et al, 2008;Kim et al, 2011;Thakur et al, 2016). In the current study, multiple daily intrathecal injections of siRNA/IL-10 receptor-␣ progressively induced mechanical allodynia in the contralateral hindpaws, although it did not further attenuate the reduced withdrawal thresholds in the ipsilateral paws, which may be due to the ceiling effect.…”
Section: Discussionmentioning
confidence: 99%
“…Exenatide also showed neuroprotection in a mouse model of multiple sclerosis (Aharoni et al, 2011;Hölscher, 2012Hölscher, , 2014. In addition, we recently reported that activation of spinal GLP-1 receptors produced marked antinociception in a variety of rodent models of chronic pain, including neuropathic, inflammatory, bone cancer, and diabetic neuropathic pain (Gong et al, 2014a;Gong et al, 2014b;Zhu et al, 2014;Fan et al, 2015;Xu et al, 2017). Interestingly, GLP-1 receptor agonists have been in clinical trials to assess their neuroprotective effects on patients with Parkinson's disease (www.clinicaltrials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of GLP-1Rs in the central nervous system also mediates neuroprotection in preclinical animal models of neurodegenerative disorders, including Parkinson disease, Alzheimer disease, amyotrophic lateral sclerosis, multiple sclerosis, peripheral neuropathy, and ischemia and stroke (Kim et al, 2009;Harkavyi and Whitton, 2010;Hölscher, 2012;Hansen et al, 2015;Jia et al, 2015). Our laboratory also recently revealed that agonism of spinal GLP-1Rs by peptidic, nonpeptidic, and herbal iridoid agonists produced antinociception in a variety of rodent pain models of neuropathy, inflammation, bone cancers, and diabetes (Gong et al, 2014b;Zhu et al, 2014;Fan et al, 2015;Xu et al, 2017). The GLP-1R in pancreatic islet b cells evokes insulin synthesis during episodes of hyperglycemia (Baggio and Drucker, 2007;Lee and Jun, 2014).…”
Section: Introductionmentioning
confidence: 93%